An endotracheal ectopic parathyroid Adenoma mimicking asthma - Seyhan, Ekrem (Amer Coll Chest Physicans, 2015)
INTRODUCTION: Ectopic parathyroid glands can be seen from the front of the bifurcation of carotis to pericardium (1). In this case report an ectopic parathyroid adenoma (EPA) obstructing the tracheal lumen, locating in the distal part of the trachea is presented. It has never been reported in the literature before.
WOS: 000366134400004
Keywords: Asthma; Endotracheal; Ectopic; Parathyroid